First case of near haploid philadelphia negative B-Cell acute lymphoblastic leukaemia relapsing as acute myeloid leukemia following allogeneic hematopoietic stem cell transplantation. (2020) - Horgan, Claire; Kartsios, Charalampos; Nikolousis, Emmanouil; Shankara, Paneesha; Kishore, Bhuvan; Lovell, Richard; Murthy, Vidhya; Rudzki, Zbigniew; Dyer, Sara; Holtom, Pam; Thompson, Gillian; Kaparou, Maria; et al.
Abstract: Herein we present a female patient aged 61 with Philadelphia negative acute lymphoblastic leukaemia demonstrating near haploid karyotype and abnormal TP53 expression at diagnosis, who relapsed with lineage switch as Acute Monocytic Leukemia post allogeneic stem cell transplantation. Molecular analysis established that both neoplasms were derived from the same founder clone. The leukemic lineage switch phenomenon has recently re-attracted interest as mechanism of leukemic evasion post treatment with chimeric antigen receptor T-cells but there is paucity of data on its presence post allograft or following novel antibody treatments such as Inotuzumab Ozogamicin or Blinatumomab. Our proposition for cancer research is that near haploidy in ALL could be linked to leukemic stem cell plasticity evading stem cell transplantation and other immunotherapy approaches.